Navigating Adolescent Health and Aesthetic Imperative: A Qualitative Study of Adolescence in Islamabad - Warda Waheed; Abdul Qadar (Life and Science)
Objective: This paper aims to understand the relationship between adolescence, aesthetic imperative, and health in the larger socio-cultural context of Islamabad, a representative urban area of Pakistan. Study Design: Qualitative research design comprises participant observation, unstructured interviewing and focus group discussions. Place and Duration of Study: The study was conducted among the adults of Islamabad from August 2022 to November 2022. Places of participant observation, interviews and focus group discussions vary from neighborhoods of a gated community of Islamabad, university cafeteria, and classrooms of the National University of Medical Science Rawalpindi, Pakistan. Methods: Overall, a qualitative research framework has been designed for data collection through unstructured interviews (stretching from somewhat formal interviews to normal conversation in the form of jokes, etc.), focus group discussions, and participant observation, yielded emic perspectives and subjective experiences of adolescents of Islamabad. The argument has been established on the basis of thematic analysis of the empirical evidence leading to the conceptualization of the themes. Results: It is found that adolescence is considered a crucial phase of life because it shapes the trajectory of life in significant ways. Adolescents refer to the numerous physical and cognitive changes shaping their individual experiences as a period of stress and storm, resulting in high susceptibility to health hazards for adolescents. However, many of these hazards are based on sociocultural grounds that necessitate medical regimens among adolescents. One of the important dimensions of medicalization, which is found prevalent among this age group, is aestheticization as a part of the modern aestheticized culture influenced mainly by the contemporary media landscape. Conclusion: The narratives present a mix of intrinsic factors and dimensions of socialization that impels them to resort to an aesthetic imperative.